2006
DOI: 10.1051/rnd:2006014
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal developmental changes in glucose transporters, intermediary metabolism and hormonal receptors related to the IGF/insulin-glucose axis in the heart and adipose tissue of bovines

Abstract: -Glucose transporter ontogenesis is likely to play a key role in glucose uptake by foetal tissues in order to satisfy their energy requirements. We thus investigated developmental changes in the bovine heart and perirenal adipose tissue in two glucose transporter isoforms, namely GLUT1 and GLUT4, the latter being responsible for the regulation of glucose uptake by insulin. Other key players of the glucose/insulin axis were also assessed. Plasma glucose concentration in the foetus was lower at 8 and 8.5 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…The genetic correlation of IMF content is on average positive with tenderness (r G 5 0.41) or negative with Warner-Bratzler shear force (r G 5 20.50) in cattle. As marbling score in these animals is genetically highly correlated with muscle lipid content (r G 5 0.91), selection based on the former may lead to a correlated improvement in tenderness (for review, see Hocquette et al, 2006). This relationship explains most of the efforts dedicated to the development of live scanning for IMF content as a selection tool in the United States and Australia (Reverter et al, Intramuscular fat content in meat-producing animals 2000; Hassen et al, 2001;Sapp et al, 2002).…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 99%
“…The genetic correlation of IMF content is on average positive with tenderness (r G 5 0.41) or negative with Warner-Bratzler shear force (r G 5 20.50) in cattle. As marbling score in these animals is genetically highly correlated with muscle lipid content (r G 5 0.91), selection based on the former may lead to a correlated improvement in tenderness (for review, see Hocquette et al, 2006). This relationship explains most of the efforts dedicated to the development of live scanning for IMF content as a selection tool in the United States and Australia (Reverter et al, Intramuscular fat content in meat-producing animals 2000; Hassen et al, 2001;Sapp et al, 2002).…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 99%
“…Available data on genes and enzymes of the main lipogenic pathways in ruminants has been recently reviewed (Bernard et al, 2008). Similar precursors and lipogenic pathways are probably involved in TAG deposition Bonnet, Cassar-Malek, Chilliard and Picard in perirenal BAT of ovine (Vernon, 1986) and bovine Hocquette et al, 2006) foetuses.…”
Section: Dynamics Of At Growthmentioning
confidence: 99%
“…To date, only HSL has been identified in bovine WAT through its mRNA abundance (Bonnet et al, 1998;Sumner and Mcnamara, 2007;Xu et al, 2008) and its activity (Sprinkle et al, 1998;Kazala et al, 2003). The thermogenic protein UCP1, together with enzymes involved in the citric acid cycle and the respiratory chain, are expressed in bovine foetal BAT, allowing FA oxidation and heat production (Casteilla et al, 1989;Smith et al, 2004;Hocquette et al, 2006).…”
Section: Dynamics Of At Growthmentioning
confidence: 99%
“…Mooradian et al have reported that thyroid hormones have different effects on GLUTs expression during development and in adulthood [32]. Furthermore, thyroid hormones have species-specific and tissue-specific effects on GLUT1 and GLUT4 expression in insulin sensitive tissues [25, 32, 60]. During fetal life, GLUT1 is predominant in insulin sensitive tissues and transition of this dominancy to GLUT4 after birth is regulated by thyroid hormones [25, 26].…”
Section: Discussionmentioning
confidence: 99%